Quality analysis of milk stored in vertical chiller coupled with solar photovoltaic system - Kumar, Ashok; Jain, Sanjay Kumar; Jain, Narendra Kumar; Lakhawat, Shreedhar Singh; Goyal, Arun Kumar; Panwar, Narayan Lal (Journal of Postharvest Technology, 2023)
The present study was carried out to know the quality of milk stored in solar-based milk chiller. A 40 lit capacity of milk chiller was tested with no  load and full load condition. In full load, milk was loaded and the temperature of the milk was recorded for every 10 min of interval. Quality  analysis of raw milk, as well as chilled milk for the duration of 0, 12, 24, 36 and 48h, were analysed. The average initial temperature of raw milk  was found to be 34.4°C. The milk temperature in the chiller was reduced to 4ºC in 100 min, which was within the recommended milk cooling  time after milking (WHO). The final temperature of the milk varied depending on the loading of the milk as well as the influence of the agitation.  There were no significant variations observed in the quality parameters of raw and chilled milk. The developed solar photovoltaic milk cooling  unit may be recommended for small use where electricity is the main constraint.
Keywords: Milk chiller; fat; SNF; acidity; milk quality